Ethics and Methodology in Legal Theory a (Personal) Research Anti-Manifesto - M. Davies (Law Text Culture, 2002)
The attitude of the critical researcher, as opposed to the traditional researcher into 'objective' knowledge, lies in the conviction that the theorist-researcher is no mere observer or discoverer of knowledge, but is herself embedded in the social, historical, political context in which knowledge is formed (Horkheimer 1968). The critical researcher therefore aims to be self-reflective, and attentive to the conventional dimensions of scholarship. Some methodological questions for the critical researcher might be -- what are the norms of 'good' scholarship, where do these derive from in cultural or political terms, on what basis can they be defended, and how should they be challenged or re-formed? Another question of some significance is -- how do ethical and political beliefs influence the substance and methodology of research? This is the issue which I want to focus upon in this brief article, focusing particularly upon methodology.